Does satisfaction after watching the trailer affects online streaming movies subscription? Empirical study on Netflix - Farah Qisthina; Hendy Mustiko Aji (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
This study is purposed to test the factors that encourage consumers to subscribe to Netflix. The sample in this respondent is selected using a purposive sampling technique with the criteria of all Indonesians who have watched trailers of several Netflix films in various media. The number of valid respondents is 222. All data are analyzed using the PLS-SEM method. This study indicates that subscription intention to Netflix is significantly affected by brand image, trailer satisfaction, and the quality of Netflix service. In addition, the brand image in this study also has a significant connection to Netflix trailer satisfaction. However, service quality has insignificant effect on trailer satisfaction. These findings are expected to help Netflix improve the quality of its service to increase customer satisfaction and maintain Netflix's image to stay good so that customers intend to subscribe to Netflix.